KEBIJAKAN PEMBANGUNAN “SIJORI” DAN DAMPAKNYA TERHADAP KEBUDAYAAN - Aribowo, Sutamat (P2KK LIPI, 2009)
In the New Order era, President Soeharto, Prime Minister Mahathir Muhammad, and Prime Minister of Lee Kuan Yew developed a cooperation among three nearby states, which called “growth triangle” Singapura - Johor - Riau (Sijori). The approach used at that moment was “comparative advantage”. As a consequence of this approach, its orientation tends to be more quantitative rather than qualitative. Caring less for the qualitative issue has made the approach ‘ignore’ the problems of culture. Therefore, policies executed following the paradigm of “growth triangle” Sijori were merely seen from the perspective of economic and politics. This article tries to reflect and converse the cooperation of “growth triangle” in Kepulauan Riau from the perspective of culture. Particularly in answering the question on how the policies of culture in this area at past, present, and the future are. Keyword: Politics of culture, development policy, Sijori, Malay’s world.